Design and ecological thinking. The new narratives of contemporary design placing Earth on centre stage - Alessandro Valenti; Andrea Trimarchi and Simone Farresin (Agathón)
Transcending design as a blueprint (of an object) to enter the realm of inquiry in an era of climatic and social instability, incorporating knowledge and observing and revealing the phenomena around us from a design perspective: these are all themes addressed by this paper in an attempt to reknit the frayed threads of a discipline frequently called upon to speak of the ecological transition. Recalling Buckminster Fuller, who promoted a practice of design based on rigorous analysis and transparency between both material and user, the design approach of Studio Formafantasma in recent years has been adopted as a paradigm in an alternative to the status quo. With their experimentation, research and, above all, questions, the studio attempts to imagine different futures by revealing the limits of the mannerist creativity embedded in a certain way of thinking about design. In this way, the studio with a documentary-like flair produces information and communication without resigning itself to dominant narratives, nor to the boundaries between species or forms of knowledge.